2020
DOI: 10.1101/2020.07.07.191239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Weather and Season on Human Brain Volume

Abstract: AbstractWe present an exploratory cross-sectional analysis of the effect of season and weather on Freesurfer-derived brain volumes from a sample of 3,279 healthy individuals collected on two MRI scanners in Hartford, CT, USA over a 15 year period. Weather and seasonal effects were analyzed using a single linear regression model with age, sex, motion, scan sequence, time-of-day, month of the year, and the deviation from average barometric pressure, air temperature, and humidity,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Further, (Pantazatos, 2014) found significant annual periodicity in the left superior temporal gyrus (STG) and grey matter volume, with a peak towards the end of December. Finally, (Book et al, 2020) found positive relationships between left and right cerebellum cortex and white matter between seasons (the comparisons of January/June and January/September) and negative relationships between several subcortical ROIs for the summer months compared to January.…”
Section: Resultsmentioning
confidence: 92%
“…Further, (Pantazatos, 2014) found significant annual periodicity in the left superior temporal gyrus (STG) and grey matter volume, with a peak towards the end of December. Finally, (Book et al, 2020) found positive relationships between left and right cerebellum cortex and white matter between seasons (the comparisons of January/June and January/September) and negative relationships between several subcortical ROIs for the summer months compared to January.…”
Section: Resultsmentioning
confidence: 92%
“…It has been theorized that prior history of repeated sub-concussive head impacts could change one's biological threshold for a concussion, 55 and there is mixed evidence to support this. [15][16][17][18][56][57][58][59] Additionally, cross-sectional data suggests that brain volume changes seasonally in the general population, 60 and this could theoretically influence concussion risk over the course of a season, regardless of game conditions or cumulative impact exposure.…”
Section: Explanatory Mechanismsmentioning
confidence: 99%